O trabalho segundo a visão de um grupo de aposentados - Chrisostomo, Alessandra Cássia Ribeiro (2009)
This study aims to know and understand the meaning of philosophies, expectations and needs of retirees, with the continuity or interruption of work when they retire. In our society, the work is the privileged place of social references. Each person invests more or less in their professional role according to their needs, their motivations and aspirations. Order to further investigate this phenomenon, we conducted a survey where nine respondents were retired from the AAPS, men or women, socio-economic strata of middle and high population, and two retirees with a high school degree and seven retirees with higher education. Of these nine, three stopped working after retirement, three stopped and returned and three remained professionally active. The methodology used was based on qualitative research design of collective case study. By analyzing the content of the interviews, were constructed categories relate to the subject and discuss the data found. Results showed that both groups of retirees who remained professionally active have a more optimistic view of aging by giving them positive aspects such as stage of peace, maturity, and expectations about the future. The group of pensioners who stopped working, had a melancholy view of old age, when one lives past experiences, without any link with the future. Despite the aging s most positive view has been attributed by the groups who remained professionally active, the main reason for the continuation of the work or the resumption of this was not financial, nor has the bonus of the work itself, but the difficulty in staying in their homes. Only one of the interviewees, a man of the group member who continued working, reported that the reason he did continue was that he loves what he does and because of financial aid from it. Another retiree, also male and belonging to this group, mentioned the financial factor, but it was noticed in his narrative a certain dissatisfaction with his job, which is a way to occupy him and not to enrich him professional or personally. One of the most relevant results was that four retirees assigned to work was the only reason for their lives, and there was no motivation to stop working, revealing the failure to develop a close relationship with their families. This finding brings into discussion the importance of human relations inside and outside the family. Loneliness is a major threat to the retirees. They must be accepted and valued. Therefore, it is important to highlight the significance of their presence within the family, for everything that they lived for and the activities that they could do. So it is in the family that retiree can look for resources to be able to live their new journey, this stage of confrontation of dreams, loss and new reality, more emotional and creative, but it is necessary to have the family around at all moments of life